Acute endocrine, immune, and muscle damage responses following a 2,000-m rowing time trial in elite male athletes - Ha, S.-M.; Ha, M.-S.; Lee, M. (Frontiers in Physiology, 2025)
Background: Rowing is a whole-body sport characterized by high-intensity efforts that require simultaneous aerobic and anaerobic energy provision. Although endurance physiology is well documented, the acute systemic responses to competitive rowing remain insufficiently understood. The present study examined endocrine stress responses, leukocyte redistribution, and muscle damage dynamics following a 2,000-m rowing time trial in elite male athletes.